solve by elimination ie eliminate x or y from the equations by performing operations on them. first label the equations , to follow the process. x – y = 5 —————-(1) x+ y = 3 —————-(2) If (1) and (2) are added then y will be eliminated. (1) + (2) gives : 2x = 8 → x = 4 now substitute this value of x into either of the 2 equations and solve for y. let x = 4 in (1) : 4 – y = 5 → -y = 1 → y = -1 check in (1) : 4-(-1) = 4+1 = 5 check in(2) : 4 – 1 = 3

solve by elimination ie eliminate x or y from the equations by performing operations on them.

first label the equations , to follow the process.

x – y = 5 —————-(1)

x+ y = 3 —————-(2)

If (1) and (2) are added then y will be eliminated.

(1) + (2) gives : 2x = 8 → x = 4

now substitute this value of x into either of the 2 equations and solve for y.

let x = 4 in (1) : 4 – y = 5 → -y = 1 → y = -1

check in (1) : 4-(-1) = 4+1 = 5

check in(2) : 4 – 1 = 3

So your answer is x = 4 , y = -1